2017
DOI: 10.5301/ejo.5000948
|View full text |Cite
|
Sign up to set email alerts
|

Deep Capillary Macular Perfusion Indices Obtained with OCT Angiography Correlate with Degree of Nonproliferative Diabetic Retinopathy

Abstract: Optical coherence tomography angiography clearly delineated the retinal microcirculation and allowed quantification of vascular perfusion of each layer. As diabetic retinopathy progressed, a decrease in perfusion index is more pronounced in the deep retinal plexus and precedes changes in superficial plexus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
46
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 31 publications
5
46
0
1
Order By: Relevance
“…Several studies also suggest that OCTA parameter alterations in the deep vascular layer are affected more severely than in the superficial vascular layer in NPDR [10, 11, 14-16, 17, 21, 23, 26]. OCTA parameters at the deep vascular layer were most significantly affected in patients with DME [4, 29-32].…”
Section: Discussion/conclusionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies also suggest that OCTA parameter alterations in the deep vascular layer are affected more severely than in the superficial vascular layer in NPDR [10, 11, 14-16, 17, 21, 23, 26]. OCTA parameters at the deep vascular layer were most significantly affected in patients with DME [4, 29-32].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Fractal dimension in patients with NPDR was decreased in both retinal vascular layers compared to control subjects [13, 25, 27]. In contrast, another group reported increased fractal dimension in both vascular layers of patients with NPDR compared to control subjects [23]. In patients with PDR, significant FAZ area enlargement and a decrease of FAZ circularity and vessel density was detected in both superficial and deep vascular layers [28].…”
Section: Octa Parameters In the Superficial Deep And/or Intermediatmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, vascular disruption in eyes suffering from DR can be so pronounced that in two eyes deep FAZ was not completely contained in the 3 3 3-mm scan. This could be explained considering that FAZ is usually larger at deep capillary plexus, and, as already mentioned, deep vascular layer disruption is more pronounced in DR. 17,28 With regard to vessel density, our study showed a poor interchangeability across different angiocubes for every plexus and every subgroup. Several aspects should be considered to interpret this finding.…”
Section: Discussionmentioning
confidence: 99%
“…The deep plexus is considerably disrupted in DR patients, especially in cases of severe retinopathy. 28 In addition, diabetic macular edema is associated with the involvement of the deeper retinal layers and, thus, it can also affect FAZ measure. 29,30 Because the 12 3 12-mm angiocube has a poor resolution, it can be more difficult to unequivocally outline FAZ area compared with smaller scans.…”
Section: Discussionmentioning
confidence: 99%